A covalent organic framework with a self-contained light source for photodynamic therapy. Issue 34 (7th April 2022) - Ren, Wen-Xiu; Kong, Fei; Shao, Yu-Qing; Huang, Qing-Yun; Sun, Long-Fei; Feng, Jie; Dong, Yu-Bin
Abstract : A nanoscale luminol-loaded and Fe(iii )-doped porphyrin-COF with a self-contained light source for photodynamic therapy is reported. Abstract : External light-independent antitumor PDT is successfully realized with a covalent organic framework (COF)-based host–guest nanosystem. Its highly effective antitumor behavior is fully demonstrated by both H2 O2 -overexpressed 4T1 and H2 O2 -less expressed HCT116 and MCF-7 xenograft models.